2021
DOI: 10.1177/19458924211061442
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sleep Quality Following Treatment for Chronic Rhinosinusitis: A Systematic Review and Meta-Analysis

Abstract: Background Chronic rhinosinusitis (CRS) presents with broad and systemic manifestations, including impaired sleep; however, the impact of CRS treatments upon sleep is unknown. Objective To establish the effect of medical or surgical CRS treatment on subjective and objective sleep metrics for patients not previously diagnosed with sleep apnea. Methods Review of PubMed, Scopus, Web of Science, and the Cochrane Library was performed from the databases’ date of inception through August 13, 2020, for studies evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…A recent study investigated the impact of dupilumab, a monoclonal antibody inhibitor of an interleukin-4 and interleukin-13 common receptor on patients with CRSwNP: Busse et al 30 found that improvements in the SNOT-22 sleep domain scores and function domain scores were greater with dupilumab than placebo at week 24 and week 52; however, direct comparisons cannot be made as an alternative sleep domain 31 was assessed in this study. Given there are many reports of improvements in sleep quality after medical or surgical treatment for CRS, 32 our analyses provide further evidence that treatments that improve the clinical symptoms of upper respiratory tract disorders can lead to concomitant improvements in sleep.…”
Section: Discussionmentioning
confidence: 68%
“…A recent study investigated the impact of dupilumab, a monoclonal antibody inhibitor of an interleukin-4 and interleukin-13 common receptor on patients with CRSwNP: Busse et al 30 found that improvements in the SNOT-22 sleep domain scores and function domain scores were greater with dupilumab than placebo at week 24 and week 52; however, direct comparisons cannot be made as an alternative sleep domain 31 was assessed in this study. Given there are many reports of improvements in sleep quality after medical or surgical treatment for CRS, 32 our analyses provide further evidence that treatments that improve the clinical symptoms of upper respiratory tract disorders can lead to concomitant improvements in sleep.…”
Section: Discussionmentioning
confidence: 68%
“…Kawasumi et al assessed the paranasal sinus epithelium in patients with eosinophilic and non- eosinophilic CRS for the presence of two receptor molecules that have gained widespread interest as a result of the recent SARS-CoV-2 pandemic, given their role as the primary receptor for viral infection and transmission. 7 Furthermore, Fried and colleagues reviewed 16 studies in order to determine the effects of medical or surgical CRS treatment on sleep in patients not previously diagnosed with sleep apnea; 8 although subjective improvements were reported using quality of life measures, objective improvements in sleep metrics were not so readily apparent.…”
mentioning
confidence: 99%